2017
DOI: 10.1038/s41598-017-02241-x
|View full text |Cite
|
Sign up to set email alerts
|

Natural Convection Flow of a Nanofluid in an Inclined Square Enclosure Partially Filled with a Porous Medium

Abstract: This work analyses free convection flow of a nanofluid in an inclined square enclosure consisting of a porous layer and a nanofluid layer using the finite difference methodology. Sinusoidal temperature boundary conditions are imposed on the two opposing vertical walls. Nanofluids with water as base and Ag or Cu or Al2O3 or TiO2 nanoparticles are considered for the problem. The related parameters of this study are the Darcy number, nanoparticle volume fraction, phase deviation, amplitude ratio, porous layer thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(30 citation statements)
references
References 35 publications
(38 reference statements)
1
29
0
Order By: Relevance
“…Alsabery et al . 1 demonstrated nanoparticletransportation in a tilted porous cavity. They indicated that convective flow is significantly influenced by the permeable layer augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Alsabery et al . 1 demonstrated nanoparticletransportation in a tilted porous cavity. They indicated that convective flow is significantly influenced by the permeable layer augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Through numerical predictions it has been observed that thermal dissipation enrichment in an enclosure predominantly depends on the choice of nanoparticle as well as the thermal conditions. [27][28][29] Roy 30 examined nanofluid buoyant motion in the annular section between a square geometry and three distinct interior geometries, such as circular or elliptical or rectangular cylinder and found the inner shapes has profound impacts on thermal dissipation rates compared to a square geometry. Using combined Lagrangian and Eulerian modeling, Sharaf et al 31 investigated the convective motion and nanoparticle dissemination in a microchannel formed by parallel plates and brought out inaccuracies in the existing nanofluid model.…”
Section: Introductionmentioning
confidence: 99%
“…Sheikholeslami et al 7 probed the Coulomb force influence on the heat transfer of a nanofluid. Alsabery et al 8 presented the nanofluid flow in an inclined enclosure with a porous medium. Sheikholeslami 9 probed the flow of nanofluid in porous media.…”
Section: Introductionmentioning
confidence: 99%